2021
DOI: 10.13189/saj.2021.090326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fundamental Motor Skills Intervention Program on Kindergarten Students

Abstract: Background: The ability of motor skills becomes the basis for children to master movement skills. There are still many students whose motor skills are below average. Objective: The aim is to compare the fundamental motor skills (FMS) regular program with the intervention FMS program conducted in 12 meetings within 6 weeks in schools. Methods: 80 kindergarten students were sampled and split into two equal groups where 40 students were placed in the control group to receive regular training and the rest 40 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…A clear sex interaction effect was also revealed that showed that girls reacted differently and more positively to the intervention than boys, especially regarding their locomotor skills (LTRS) and the sustainable effect of the programme on these skills. Girls in both groups outperformed their male counterparts in locomotor skills proficiency at pre-testing, which is consistent with the findings of FMS-based intervention studies (Chan, Ha & Ng 2016;Kelly et al 2021;Logan et al 2012;Morgan et al 2013;Palmer et al 2019;Pranoto et al 2021;Wick et al 2017). Studies by Barnett et al (2009) on 8-10-years-old rural Australian children, 4-5-yearsold Australian preschool children (Hardy et al 2010) and 6-9-years-old Irish primary school children (Bolger et al 2018) have also reported girls having higher locomotor scores than boys.…”
Section: Discussionsupporting
confidence: 82%
“…A clear sex interaction effect was also revealed that showed that girls reacted differently and more positively to the intervention than boys, especially regarding their locomotor skills (LTRS) and the sustainable effect of the programme on these skills. Girls in both groups outperformed their male counterparts in locomotor skills proficiency at pre-testing, which is consistent with the findings of FMS-based intervention studies (Chan, Ha & Ng 2016;Kelly et al 2021;Logan et al 2012;Morgan et al 2013;Palmer et al 2019;Pranoto et al 2021;Wick et al 2017). Studies by Barnett et al (2009) on 8-10-years-old rural Australian children, 4-5-yearsold Australian preschool children (Hardy et al 2010) and 6-9-years-old Irish primary school children (Bolger et al 2018) have also reported girls having higher locomotor scores than boys.…”
Section: Discussionsupporting
confidence: 82%
“…In this sense, it is recognized that childhood is a fundamental stage to promote the acquisition of healthy habits, practice physical activity, and ultimately achieve optimal development [5][6][7], which allows an adult life free of diseases physically, organically, and cognitively [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because exercise has many benefits for the mother and fetus, lo. For example, strengthen the baby's heart [22]- [23]. According to experts in the US National Library of Medicine -National Institute of Health, regular exercise is very beneficial for the baby's heart.…”
Section: Discussionmentioning
confidence: 99%